Achieving universal health care coverage: Current debates in Ghana on covering those outside the formal sector - Abiiro Gilbert; McIntyre Di (BMC, 2012)
Abstract Background Globally, extending financial protection and equitable access to health services to those outside the formal sector employment is a major challenge for achieving universal coverage. While some favour contributory schemes, others have embraced tax-funded health service cover for those outside the formal sector. This paper critically examines the issue of how to cover those outside the formal sector through the lens of stakeholder views on the proposed one-time premium payment (OTPP) policy in Ghana. Discussion Ghana in 2004 implemented a National Health Insurance Scheme, based on a contributory model where service benefits are restricted to those who contribute (with some groups exempted from contributing), as the policy direction for moving towards universal coverage. In 2008, the OTPP system was proposed as an alternative way of ensuring coverage for those outside formal sector employment. There are divergent stakeholder views with regard to the meaning of the one-time premium and how it will be financed and sustained. Our stakeholder interviews indicate that the underlying issue being debated is whether the current contributory NHIS model for those outside the formal employment sector should be maintained or whether services for this group should be tax funded. However, the advantages and disadvantages of these alternatives are not being explored in an explicit or systematic way and are obscured by the considerable confusion about the likely design of the OTPP policy. We attempt to contribute to the broader debate about how best to fund coverage for those outside the formal sector by unpacking some of these issues and pointing to the empirical evidence needed to shed even further light on appropriate funding mechanisms for universal health systems. Summary The Ghanaian debate on OTPP is related to one of the most important challenges facing low- and middle-income countries seeking to achieve a universal health care system. It is critical that there is more extensive debate on the advantages and disadvantages of alternative funding mechanisms, supported by a solid evidence base, and with the policy objective of universal coverage providing the guiding light.